Clinical and epidemiological aspects of hepatitis C cases in the State Of Maranhão, Brazil (Research, Society and Development, 2020)
Viral hepatitis is an infectious disease with a high universal morbidity and is an important public health problem. The aim of this study was to analyze the clinical and epidemiological profile of hepatitis C cases in the state of Maranhão. This is an epidemiological, retrospective and descriptive study of a population nature, using secondary data, in which a case study for types C viral hepatitis reported in the period from 2009 to 2018, obtained from the Health Information System of Notification (SINAN). Aspects related to gender, age group, race, education, mechanical source of infection, final classification, clinical forms and laboratory diagnosis and finally the number of cases in the State were evaluated. The data were tabulated using the TABNET and Microsoft Office Excel 2019 programs. During the research period, 1584 cases of hepatitis C were found, where the largest number of cases was in 2011, totaling 223 notifications (14%) and the lowest corresponded to 2017 (5.55%). The individuals most affected by the disease were male (55.7%), aged between 40 and 50 years (53.9%). The predominant ethnic group was mixed race (51.6%) and 25.3% of the patients had completed high school and the main source of infection was sexual (11.6%) and transfusion (10.8%). The chronic form of notified hepatitis C cases corresponded to 89%. While the form of laboratory diagnosis was anti-HCV. These data allow guiding public health decisions, contributing to the planning, management and evaluation of interventions for the control and prevention of hepatitis C in Maranhão.